1981
DOI: 10.1097/00000658-198111000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Micro- and Macrometastases in Breast Cancer

Abstract: Recurrence and survival data at 10 years were examined for 147 women with single axillary lymph node metastases found in a modified radical or standard radical mastectomy. The cases were identified through a review of all patients with primary operable breast cancer treated at Memorial Hospital from 1964 to 1970. The patients were stratified into groups according to size of the primary tumor and of the metastatic deposit (micro less than or equal to 2 mm; macro greater than 2 mm) as well as level of the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(75 citation statements)
references
References 6 publications
2
72
0
1
Order By: Relevance
“…Some studies have classified nodal metastases according to size, using the term micrometastases for small deposits, but the cut-off has ranged between 0.2 and 2 mm. Although there is evidence that larger axillary nodal metastases are associated with a worse prognosis (Huvos et al, 1971;Fisher et al, 1978;Rosen et al, 1981;Nasser et al, 1993;McGuckin et al, 1996;Cote et al, 1999), this is not so in all studies (Wilkinson et al, 1982;Hainsworth et al, 1993) including the present one. Only two studies, however, included multivariate analysis.…”
Section: Discussionmentioning
confidence: 61%
“…Some studies have classified nodal metastases according to size, using the term micrometastases for small deposits, but the cut-off has ranged between 0.2 and 2 mm. Although there is evidence that larger axillary nodal metastases are associated with a worse prognosis (Huvos et al, 1971;Fisher et al, 1978;Rosen et al, 1981;Nasser et al, 1993;McGuckin et al, 1996;Cote et al, 1999), this is not so in all studies (Wilkinson et al, 1982;Hainsworth et al, 1993) including the present one. Only two studies, however, included multivariate analysis.…”
Section: Discussionmentioning
confidence: 61%
“…It has been suggested that the amount of regional lymph node involvement is associated with a worse patient prognosis (24,25). To determine whether hypermethylation profiling of the primary tumor was associated with lymph node tumor burden, patients were categorized according to the size of the SLN metastasis as accepted by the American Joint Committee on Cancer Staging Manual sixth edition (26): macro, >2.0 mm (n = -41); micro, V2.0 mm but >0.2 mm (n = 40); and none (n = 70), absence of tumor identification following H&E and immunohistochemistry staining.…”
Section: Resultsmentioning
confidence: 99%
“…A case controlled study of 96 patients with 15 year follow-up has found that occult MM in ALNs appears to predict subsequent distant metastases in patients with stage 1 BC [32]. There are several other studies which have found a significantly poorer prognosis associated with MM [33,34]. In a prospective study of women with stage 1 BC, the International Ludwig Breast Cancer Study Group reported a 5-year disease free survival of 58% in patients with MM compared with 74% in those without and overall survival rates of 79% and 88%, respectively [35].…”
Section: Analysis Of the Sentinel Lymph Nodementioning
confidence: 99%